The Probe Team [episode no. 281] - Bayle, Anna. (Quezon City Probe Productions, 1994)
Impasse deals with the issue on Total Log Ban bill. Duty-Free Philippines competing with other department stores is protrayed in Fearing Duty-Free. An exclusive interview of the most successful ramp model is seen in the lasr part.
Impasse (15 min.) -- Fearing Duty-Free (20 min.) -- Anna Bayle (15 min.)
Keywords: Duty-Free Philippines; Logging -- Philippines; Shopping centers -- Philippines; Models (Persons).